Code Spelunking Redux. - NEVILLE-NEIL, GEORGE V. (Communications of the ACM, 2008)
The article discusses computer programming, examining the complexity of the computer code required by increasingly complex systems. The tools used to understand the complex systems have not grown at the same rate, size, or scope as the systems in question. Topics of discussion include Moore's law regarding the power of computers, code from outside sources integrated by software teams, and complex interactions between systems. Also discussed are systems calls provided to user programs by an operating system (OS) kernel.